Factors Associated with Teenage Pregnancy: A Hospital-Based Case-Control Study - Bhusal, Chet Kant; Bhattarai, Sigma; Myia, Salau Din; Adhikari, Kishor; Shrestha, Saneep; Pokhrel, Gunjan (Journal of Karnali Academy of Health Sciences, 2024)
Background: Teenage pregnancy is a major public health problem and is considered to be high risk for maternal health, pregnancy outcomes, and long-term effects. This study aims to determine the factors associated with teenage pregnancy among pregnant teenagers and non-teenagers in a tertiary hospital of Nepal. Methods: A hospital-based case-control study was conducted using 1:2 case-control ratio among 109 pregnant teenagers and 218 non-teenage pregnant women attending antenatal service at a tertiary hospital of Rupandehi, Nepal, from October 2020 to February 2021. Two controls were selected on the same day when a case was identified. Variables found significance (p<0.05) in bivariate analysis were entered into multivariable logistic regression to identify final associated factors. Results: The mean age of cases was 17.81± 1.01 years, while controls were 25.35 ± 2.46 years. Women from Dalit caste (AOR=3.04, CI=1.02-9.07), engaged in business work (AOR= 0.23, CI= 0.10-0.57), food sufficiency for more than 12 months per year (AOR =2.83, CI= 1.09-7.31), family planning (AOR=2.38, CI=1.33-4.25) and anemia (AOR= 2.58, CI: 1.56-4.27) were positively associated with teenage pregnancy. Conversely, primary (AOR= 0.18, CI= 0.06-0.57), secondary (AOR= 0.13, CI= 0.06-0.26) and SLC and above education (AOR= 0.36, CI= 0.15-0.85) were found to be negatively associated. Conclusions: Ethnicity, education, occupation, food sufficiency, family planning use and hemoglobin were found to be independently associated factors of teenage pregnancy. Thus, policy makers and administrators should focus on informal educational intervention, intervention for utilization skills of family planning, and nutrition promotion during pregnancy especially for disadvantages people.